MAQĀSID AL-SHARĪ’AH: Solusi Atas Problematika Kontemporer - Nurhadi, Nurhadi; Yumna, Laila (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
The fast moving dynamics of life necessitate changes in all aspects of life, as well as giving rise ti fiqh problems whose complexity requires the creativity if Islamic law jurists to be able to formulate appropriate methodologies to answer the problems. Even though it can no longer be called a contemporary method, the formulation of the legal istinbath method within the framework of maqasid al-shari’ah can be used a methodological solution to answer the challenges and changes of the times.